A mind for business : get inside your head to transform how you work - Gibson, Andy, 1977- (Always learning., 2015)
Using the most effective insights from psychology and neuroscience you can be more effective, more resourceful and develop the sharpest of business brains. 'A Mind For Business' has recently been shortlisted for the CMI Management Book of the Year Awards!